Curriculum of Children’s Education in the Hadith of Muḥammad the Prophet - Anshar, Muhammad Fakhrurrazi; Lubis, Tonang (Advances in Social Sciences Research Journal, 2021)
The family is the first and basic institution among the various responsible social institutions for preparing the child to enter social life, to be a good and effective element in its maintenance on the basis of righteousness, goodness and effective construction. It is the starting point that affects all stages of life, positively and negatively. The first is the marital relationship through birth, nursery, pre-puberty and ending with complete independence after the self-reliance. Childhood took a large part in the Hadiths of the Messenger of God, and the scholars of Hadith who unanimously agreed on the honorable Sunnah of the Prophet took care of this aspect, and they did not neglect the provisions and manners related to the child in all of their books in the field of Hadith. We will follow in this study, the method of children’s education, which was mentioned by the hadiths of the Noble Prophet. The Messenger of God, gave the birth of a child a dignified care, for he birth of a child is not an ordinary matter that passes without attention. It is the right of the newborn baby to be called and choose a good name for him, to remove the harm from him, to be tender, to be called upon, to bless him, to teach him and to watch him, and to treat him.